Аналіз комп'ютерних систем візуалізації з метою алгоритмізації обґрунтування щодо їх використання - Дрєєв, О. Д.; Железняк, Б. Ю.; Drieiev, O.; Zhelesnyak, B. (ЦНТУ, 2021)
Проектування програмного забезпечення передбачає використання кількох фреймворків, які хоч і скорочують час розробки програмного забезпечення, але мають свої можливості, недоліки та переваги. Використання фреймворка також накладає на проект певні архітектурні особливості, які залежать від обраного каркаса. Тому перед інженером-програмістом постає інтелектуальне завдання створення архітектури програмного забезпечення з вибором із ряду доступних фреймворків та з урахуванням їх впливу на функціонування системи в цілому. Результат проектування є важливим кроком, який може вплинути на успіх проекту. Тому в даній роботі розглядається проблема посилення об’єктивної складової у процесі вибору фреймворку, зокрема системи комп’ютерної візуалізації при створенні архітектури програмного забезпечення. В результаті запропоновано метод вибору системи візуалізації, який базується на аналізі завдань до системи візуалізації з виведенням вимог до побудованого зображення. Показано застосовність багатокритеріальної оптимізації для поділу застосовуваних систем візуалізації та вибору найкращої з них. Designing modern software involves the use of several frameworks. The framework reduces software development time. But frameworks have their own capabilities, disadvantages and advantages. The use of the framework also imposes certain architectural features on the project. Therefore, the engineer faces the intellectual task of creating a software architecture when you need to choose from an available set of frameworks and take into account the impact of these frameworks on the functioning of the system as a whole. The design result is an important step that has an impact on the success of the project. Therefore, this paper considers the problem of strengthening the objective component in the process of choosing a framework, namely the computer visualization system when creating a software architecture. As a result, a method for selecting a visualization system is proposed. This method is based on the analysis of tasks that are put forward in the visualization system, taking into account the requirements for the image to be built. On the basis of the formed tasks to the visualization system, the article synthesizes the requirements for the visualization systems. Also, according to experts, the importance of compliance with certain requirements is assessed. According to the characteristics of computer visualization systems and quantitative values, the evaluations provided by experts show the applicability of multicriterial optimization to separate the applicable visualization systems and choose the best one. In order to illustrate the choice of computer visualization system, the article uses an example of applying the method to a turn-based strategy game. The result is a method for selecting computer visualization systems, which is based on the created classifications of tasks facing the visualization system. The relationship between the purpose of the visualization system and the list of tasks that the visualization system must perform is shown. The paper identifies the stages that depend on subjective and objective factors. The results allow a structured approach to computer visualization systems in the software architecture design process.
Analysis of Computer Visualization Systems in Order to Algorithmize the Rationale for their Use
Keywords: проектування; програмне забезпечення; прийняття рішення; комп’ютерна система візуалізації; design; software; decision making; computer visualization system